Propagación vegetativa por estacas de ocho especies forestales - Zanoni Mendiburu, Carlos A. (Universidad de Costa Rica, San José (Costa Rica) CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag.Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1975